Kaf'ah Ignore Factors in Marriage (Case Study in Bale Busu Village, Mutiara Subdistrict, Pidie Regency) - Afrizal; Eva Solina; Saifan Riza (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Kafa'ahis an alternative for people who want to do marriage in choosing their partner. It is prescribedkafā'ahis to form a sakian household, mawaddah and rahmah. In general, people's understanding of the meaning ofkafā'ahalready understand, but many people ignore it due to certain things. This research is a field research with a qualitative approach. The data sources are primary data sources and secondary data sources using two data collection techniques, namely interview and observation data collection techniques. The results of his research show thatfactors that influence people to ignore kafaah are: (1) prefer a partner who has religious knowledge (2) kafā'ah is not a legal requirement for marriage; (3) Economic Factors (4)their own intentions and arranged marriages by their parents are the causes of non-sequential marriages; (5) choose their own partner and love each other. So the conclusion is that the people of Bale Busu Village actually really understand the meaning of kafā'ah but the practice is very little from the community because it is influenced by certain factors.